Perceived effectiveness of the Career Growth & Development toolkit - Talamantez, Jonathon L. (University of Wisconsin--Stout, 2018)
With employee development become increasingly important for organizations, more and more organizations are investing in talent development solutions including career advancement opportunities. Company XYZ made a significant financial investment in the toolkit and to continue to invest in the CareerDriver, which allows employees control of their career growth and development. A challenge facing the Career Growth & Development department is the need to measure the employees' use of the toolkit and their perception its effectiveness in supporting their career development. By not having the data to evaluate the success of the CareerDriver, the CG&D department may have difficulty in leveraging the potential of the CareerDriver to help employees move their career forward. Based on the results, recommendations were made to help the organization ensure the CareerDriver provides employees with effective career development.
Keywords: Career development; Employees